Association of ambient temperature and influenza-like illness with acute appendicitis: an ecological study using 22-year data - On Tai Ken Yu; Xiaoting Jiang; Conglu Li; Yawen Wang; Yuchen Wei; Ka Chun Chong (BMC Public Health)
Abstract Background While acute appendicitis poses a significant disease burden worldwide, its etiology is not completely known. Previous studies have separately demonstrated its associations with ambient temperature and seasonal influenza, but there was no study that examined two exposures concurrently, leaving room for confounding and failing to isolate the effects of these two factors. This study aims to quantify such associations under a unified model, using population-level data in Hong Kong from 1998 to 2019. Methods The study outcome of weekly acute appendicitis admissions was analyzed with a number of covariates. The major covariates of interest included weekly mean temperature and three strain-specific influenza-like illness-positive (ILI+) rates, which were proxies for the activities of the respective influenza strains. Other covariates including weekly mean relative humidity, total rainfall and a composite index for air pollution were used for confounder control. A generalized additive model under the framework of distributed-lag non-linear model and quasi-Poisson distribution was used for multivariate analysis. Results A significant positive association between ambient temperature and acute appendicitis admission was found, with a cumulative adjusted relative risk (ARR) of 1.082 (95% CI: 1.065–1.099) comparing the 95th percentile to the median temperature. ILI + rates for influenza A/H1N1 and A/H3N2 were found to significantly and negatively associate with acute appendicitis admission, with cumulative ARRs of 0.961 (95% CI: 0.934–0.989) and 0.961 (95% CI: 0.929–0.993) respectively, comparing the 95th percentiles to zero. No significant association was found between ILI + rate for influenza B and acute appendicitis admission. Conclusions While high temperature was associated with acute appendicitis admission, a negative association of influenza infection was showed. The mechanisms underlying the above associations should be investigated in future studies, with the aim of formulating preventive strategies against acute appendicitis that take environmental exposures into consideration.